(untitled) - Kapoor, Jack R.; Jack R. Kapoor; Les R. Dlabay; Robert J. Hughes (Boston, 2005)
Personal Finance is designed to prepare high school students to make wise financial decisions in personal situations. The program helps students realize that they are already making financial decisions and shows them how their decisions affect their future. High-interest features, an engaging visual program, and easy-to-read content make the program useful for all types of learners
Keywords: Business mathematics; Finance; Personal